[The role of heat-shock proteins in recovery of high temperature induced damages of mitotic chromosomes in Drosophila melanogaster.] - Mamon, L.A.; Kutskova, Y.A. (Genetika, 1993)
The synthesis of the heat-shock proteins (HSP) and the frequency of the mitotic chromosome damages (pulverizations, chromosome, chromatid stickiness, etc.) was studied in the cells of larva nervous ganglion in the process of recovery after heat shock (37 degrees C, 30 min). Analysis was performed in two strains of Drosophila melanogaster (Canton S-the wild type and the mutant l(1)ts403 with the defect in the HSP system). Correlation between the dynamics of HSP synthesis and the alteration of the chromosome pulverization and stickiness frequency was shown for both Drosophila strains under study. These results, in accord with the data on HSPs' binding to chromosomes following heat shock and their role as molecular chaperones, allowed to suggest that HSPs took part in chromosome condensation and in the recovery of heat shock induced damages leading to chromosome and chromatid stickiness.